Efek Domino Gerakan Tiga Daerah di Bantaeng 1999-2014 - Ulil Amri; Ahmadin Ahmadin; Jumadi Sahabuddin (Pendidikan Sejarah Fakultas Ilmu Sosial Fakultas Ilmu Sosial, 2017)
This paper discusses the Movement of Kaloling, Layoa, Bajiminasa in Bantaeng 1999-2014. This study aims to discuss the background of the formation, movement patterns KANTIBMAS KALBA Bantaeng District, the movement, and the impact of movement KANTIBMAS KALBA Bantaeng District from 1999-2014. the researchers designed this research is qualitative descriptive by using historical (historical) method of writing. Through the stages of Heuristics, Criticism, Interpretation and Historiography The results of this study found that the formation and movement of KANTIBMAS KALBA Bantaeng Regency backed by a sense of disappointment of the villagers Kaloling, Layoa and Bajiminasa against security forces that are not effective in controlling the perpetrators of crime in Bantaeng District that increasingly troubling and threatening ketentraman community. In addition, the movement carried out by the KANTIBMAS KALBA Bantaeng District is stru (Anon., t.thn.)ctured neatly and very effectively so as to provide an impact that can be felt by the community by starting to control the security and public order in Bantaeng Regency. Every operation performed was a shock teraphy for the perpetrators of the crimes that made as many as 1,062. The perpetrators of crime in Bantaeng District in 1999-2003 surrendered themselves to the authorities. This success inspired other regions to form similar movements such as the Massa of Jeneponto, Massa Takalar, Massa Gowa, Bulsaumba, Sinjai, Forbes Bone and Pinrang. The researchers designed this research is qualitative descriptive by using historical (historical) method of writing. Through the stages of Heuristics, Criticism, Interpretation and Historiography